Microinvasive Invasive Glaucoma Surgery: Principles Shaping Glaucoma Surgery for the Future - Mustafa, Mohammed Sohaib (Pakistan Journal of Ophthalmology, 2015)
Over the last half century, open-angle glaucoma management has revolved mainly around topical medical treatment with or without laser trabeculoplasty, with gold standard trabeculectomy kept back for patients with advanced and progressing glaucoma. Keeping in mind the possible complications associated with trabeculectomy and glaucoma valves, 1 these are usually kept for late glaucoma treatment algorithm. Development of new topical medications has actually reduced the rate of trabeculectomy remarkably.